Nationality Expression in Architectural Form: A Response of Young People - M. Syaom Barliana, Diah Cahyani P ,Fauzi Rahmanullah (International Journal of Advanced Science and Technology, 2020)
This study aims to describe dual things. First, the perception and response of young people to the expression of nationality and diversity in architectural works (public facilities). Second, differences in perceptions and responses of young people from architecture and non-architecture students to the expression of nationality in architectural works (public facilities). This research using quantitative descriptive with three levels of analysis, consisting of descriptive analysis, differences were examined, and interpretative analysis. The research result has shown that in general, there is almost no difference in responses and perceptions between architecture and non-architecture students in evaluating the expression of nationality and unity, diversity of Indonesian culture, and pride as a nation in public architecture works in Jakarta. In general, these young people assume that the shape, style, and character of the architecture of the public building are only in the category of mediocre, which is strong enough in expressing all three aspects, and very few express themselves in the strong or very strong category.